Pengembangan Media Audio-Visual Berorientasi Tpack Dalam Pembelajaran Senam Bugar Ceria Yang Dapat Meningkatkan Motorik Anak - Lismana, Oetari; Andresta, Yulva; Kawa, Fero; Sapriyanto , Sapriyanto (Publikasi Indonesia, 2025)
The objectives of this study are to: (1) develop Tpack-oriented audio-visual media in learning cheerful fitness gymnastics that can improve children's motor skills (2) describe the effectiveness of Tpack-oriented audio-visual media in learning cheerful fitness gymnastics that can improve children's motor skills. The subjects of this study are 30 children aged 5-6 years from PAUD Aisyah, Lubuk Unen Village, Merigi Kelindang District, Bengkulu Tengan Regency, Bengkulu Province, the focus of this research is Tpack-oriented audio-visual media in learning cheerful fitness gymnastics that can improve children's motor skills. This research was conducted with a